Exotic statistics for particles without spin - Hoyuelos, Miguel Luis (2018)
The possibility of obtaining exotic statistics, different from Bose-Einstein or Fermi-Dirac, is analyzed, in the context of quantum field theory, through the inclusion of a counting operator in the definition of the partition function. This operator represents the statistical weight of the allowed number states. In particular, the statistics of ewkons (introduced in Hoyuelos and Sisterna (2016 Phys. Rev. E 94 062115)) are analyzed. They have a negative relation between pressure and energy density, a feature shared by dark energy. The present approach develops the possibility of describing dark energy with a field of non-interacting particles with ewkons' statistics.